PRONOMINA BAHASA JAWA DIALEK BANYUMAS DI KOTA PANGKALPINANG - Rahmat Muhidin (Kantor Bahasa Lampung, 2017)
AbstractThis research aims to describe personal pronouns, indifinite pronouns, and interrogative pronounsin Javanese Banyumas Dialect. This research uses descriptive method. The data were collectedthrough listening, speaking, and instrospection method. The result of the research shows thatthere are three pronouns in Javanese Banyumas dialect in Pangkalpinang (1) personal pronouns,(2) indefinite pronouns, (3) interrogativa pronouns. Personal pronouns in Banyumas language are(a) first person singular, (b) first person plural, (c) second person singular, (d) second person plural,(e) third person singular, and (f) third person plural indefinite pronouns in Banyumas language are(a) common indifinite pronouns, (b) place indefinite .pronouns, (c) interpretation pronouns. AbstrakPenelitian ini bertujuan untuk mendeskripsikan bentuk pronomina persona, pronominapenunjuk, dan pronomina penanya dalam bahasa Jawa Dialek Banyumas. Penelitian dilaksanakandengan menggunakan metode deskriptif. Data dikumpulkan melalui metode simak, cakap, danintropeksi. Hasil penelitian menunjukkan bahwa ada tiga pronomina bahasa Jawa dialekBanyumas di Pangkalpinang (1) pronomina persona; (2) pronomina penunjuk; dan (3) pronominapenanya. Pronomina persona dalam bahasa Banyumasan adalah (a) pronomina persona pertamatunggal (b) pronomina persona pertama jamak (c) pronomina persona kedua tunggal, (d)pronomina persona kedua jamak, (e) pronomina persona ketiga tunggal, dan (f) pronominapersona ketiga jamak. Sedangkan Pronomina penunjuk dalam bahasa Banyumasan adalah (a)pronomina penunjuk umum, (b) pronomina penunjuk tempat, (c) pronomina penunjuk ihwal.